CMKMS: Cluster-based mobile key management scheme for wireless sensor network. Issue 2 (27th May 2014) - Dilip Babar, Sachin; Rashmi Prasad, Neeli; Prasad, Ramjee
Abstract : Purpose: – The paper aims to address wireless sensor network (WSN) security by proposing new cluster-based mobile key management scheme (CMKMS). The growing demands of WSNs in variety of real-time and mission-critical applications increase the challenges in terms of energy efficiency, security and mobility. The security is important to avoid malicious attacks and improve the energy efficiency, while mobility helps to improve the reachability of network. The CMKMS algorithm focuses on the management and maintenance of keys under cluster-based mobile WSN network. Design/methodology/approach: – The paper studied the related work in the area of key management and compared the different key management algorithms according to the technique used. The comparative study shows that the available key management algorithms are efficient in terms of security, but they are not scaleable enough to the changing conditions of network and do not work efficiently under node mobility. The research uses cluster-based approach for improving scalability, where cluster head (CH) acts as a key manager. The work developed by considering both static and mobile CH. Findings: – The CMKMS considers two phases, first for key maintenance which establishes the two private keys, home key for own cluster and foreign key when node moves from one cluster to another. The second phase maintains the keys when CH moves from one cluster to another. The proposed algorithm improves the efficiency of key management algorithm in terms of security, mobility, energy efficiency and scalability of network. The simulation of scheme in different realistic situation shows that proposed solution shows less computational overheads, energy consumption and delay as compared with state-of-art solution. Research limitations/implications: – The research is validated using computer-based simulation, which limits the testing of research by considering external environmental conditions. Therefore, research can be further test using WSN test bed. Practical implications: – The research address the issues in key management, developed the scaleable, and node mobility supportable key management algorithms, for addressing the demands of growing WSN applications. Originality/value: – This paper accomplish the security of WSN using scaleable and mobility-supported key management algorithms.